2022
DOI: 10.1021/acs.jpcc.2c02922
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic Electrolytes Composed of LiN(SO2F)2 and Sulfones for Li-Ion Batteries

Abstract: Sulfones are polar molecules that can be used as thermally stable electrolyte solvents for Li-ion batteries (LIBs). Li salts form stoichiometric solvates with sulfones in the electrolytes. The melting points of the solvates tend to be higher than room temperature, thereby limiting the operating temperature range of the batteries. In this study, the applicability of ternary eutectic mixtures of LiN­(SO2F)2 (LiFSA), sulfolane (SL), and dimethyl sulfone (DMS) as LIB electrolytes was assessed. Relative to the bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 63 publications
(122 reference statements)
0
43
0
Order By: Relevance
“…Li salts and SL form crystalline solvates, which have melting points higher than room temperature. ,, Therefore, precipitation of the crystalline solvates often occurs in SL-based electrolytes containing high concentration Li salts. Among various Li salt/SL binary mixtures, the LiBF 4 /SL mixtures were found to maintain their liquid state over a wide temperature range even at high salt concentrations .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li salts and SL form crystalline solvates, which have melting points higher than room temperature. ,, Therefore, precipitation of the crystalline solvates often occurs in SL-based electrolytes containing high concentration Li salts. Among various Li salt/SL binary mixtures, the LiBF 4 /SL mixtures were found to maintain their liquid state over a wide temperature range even at high salt concentrations .…”
Section: Resultsmentioning
confidence: 99%
“…In these networks, Li + ions exchange ligands (solvent and anion) dynamically, and Li + -ion-hopping conduction is assumed to occur through ligand exchange. Li + -ion-hopping conduction increases the Li + -ion transference number under anion-blocking conditions (0.6–0.8), which leads to the suppression of concentration polarization in Li batteries during discharging at high current densities. ,, However, the detailed mechanism of Li + -hopping conduction in these electrolytes remains unclear. In this study, we investigated the transport properties of highly concentrated Li-salt/SL electrolytes at various temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…10. 54 Further, this electrolyte shows Li + ion-hopping conduction, and the Li + transference number is 0.45. The ionic conductivity of this electrolyte is 2.28 mS cm -1 (at 30 °C), which is considerably lower than that of a carbonate-based electrolyte, 1 mol dm -3 LiPF6 in EC/DMC…”
Section: Li-ion-hopping Conduction In Molten-solvate Electrolytesmentioning
confidence: 90%
“…Additionally, we recently found that certain HCEs exhibit a unique ion transport property, which involves conduction via a lithium-ion hopping mechanism. [13][14][15][16][17][18] The solvent-to-Li molar ratio decreases with increasing Li salt concentration in HCEs, because a greater fraction of the solvent participates in Li + solvation. Anions also are involved in Li + coordination, and contact ion pairs (CIPs) and ion aggregates (AGGs) form in HCEs.…”
Section: Introductionmentioning
confidence: 99%
“…Lithiumion hopping causes the Li + transference number in certain HCEs to become greater than 0.5, whereas this parameter is less than 0.3 in conventional 1 M electrolytes. 7,18 A large Li + transference number is advantageous in suppressing concentration polarization during high-rate charging and discharging in a battery. 19,20 One disadvantage of HCEs is their high viscosity.…”
Section: Introductionmentioning
confidence: 99%